Developmental DNA methyltransferase inhibitors in the treatment of gynecologic cancers. (11th February 2016) - Duenas-Gonzalez, Alfonso; Medina-Franco, José L.; Chavez-Blanco, Alma; Dominguez-Gomez, Guadalupe; Fernández-de Gortari, Eli
ABSTRACT: Introduction : DNA methylation has become an attractive target for the treatment of cancer. DNA methyltransferase inhibitors have proven useful for the treatment of myelodysplastic syndrome and are being evaluated in gynecological neoplasias. Areas covered : We provide an overview of the current knowledge on DNA methylation and cancer and the role of DNA methylation in cervical, ovarian and endometrial carcinomas. The results of recent clinical trials with demethylating agents for cervical and ovarian cancer treatment are also discussed. Expert opinion : There are few studies of DNA demethylating agents for cervical and ovarian cancer treatment; nevertheless, the results are promising. To accelerate these advances, there are at least two actions that can be simultaneously pursued. One is to greatly increase the number of small clinical exploratory trials with existing demethylating drugs and using methylome analyses to identify predictive factors for response and/or toxicity. The second is finding out epigenetic 'drivers' unique to gynecological cancers and their subtypes, and then proceed to clinical trials in a highly selected population of patients. It is expected that in the future, DNA demethylation could have a role in the treatment of gynecologic cancers.